Content of photosynthetic pigments in peach leaves in the humid subtropics of Russia - Ju. S. Abilfazova (Новые технологии, 2020)
Various varieties of peach as a culture with an economically profitable and high early maturity have been described; some features of the weather conditions of the Black Sea coast during cultivation is given. The results of many years of physiological research, which have been carried out in the Laboratory of plant physiology and biochemistry of the Federal Research Center «Subtropical Scientific Center of the Russian Academy of Sciences» (earlier – VNIITSISK) have been presented. The objects of the research are peach leaves of the varieties of Redhaven (control), Nicholas I (Collins clone), Larisa, Krasnaya Zarya (Redhaven clone), Comanche, Sunbeam, Spring Call (Springold clone), Summerset. It has been found that the amount of water deficit does not exceed 12,1–14,2%, and the water content of the leaf blades ranges on average from 55,2% to 70% in the varieties of Redhaven, Comanche, Summerset, Larisa. As stressful situations intensify (drought, lack of moisture in plants, high air temperature and humidity) in the subtropical zone, the Comanche, Vesennyy Prizyk and Summerset varieties show a decrease in the synthesis of a, b, chlorophyll and in the most resistant varieties of Redhaven, Larisa, Krasnaya Zarya, Sunbeam and Nicholas I show its decrease. A high content of carotenoids is up to 0,52–0,65 units.